Utilization (intifa’) of unlawful wealth acquired by unlawful means from Islamic legal perspective - Hj Ibrahim, Badruddin (Universitas Muhammadiyah Yogyakarta, 2017)
This study examines the issue of utilization (intifa’) of unlawful wealth which is acquired by unlawful means from Islamic legal perspective. The question is whether it is permissible for a Muslim to take benefit from the wealth that acquired by unlawful means? The discussion focuses on the meaning of utilization and its means; the meaning of unlawful wealth that acquired by unlawful means and its classification. It further examines the legal ruling on utilization of unlawful wealth by various means of utilizations. In addition, the study also deals with the manner in which the unlawful wealth is treated under Islamic law. The research is a library research where the issue will be examined from the perspective of the Qur’an and the Sunnah as the primary sources of Islamic law and follows with the examination of the view of Muslim jurists of four well-known schools of law as well as the view of contemporary Muslim scholars. In addition, the reference also will be made to legal opinions (fatawa) from some Muslim countries and some renowned Muslim scholars. It is hoped that the study may provide a clear reference and guideline regarding the utilization of unlawful wealth under Islamic law that is significant and beneficial to all in our present day.